Anti-influenza A virus activity of amantadine hydrochloride and rimantadine hydrochloride in ferret tracheal ciliated epithelium. - Burlington, D B (1982)
The activities and toxicities of amantadine hydrochloride and rimantadine hydrochloride against influenza A/Alaska/6/77 (H3N2) and A/Bangkok/1/79 (H3N2) viruses were compared in organ cultures and ferret tracheal ciliated epithelium. Pretreatment of cultures with concentrations (0.5 and 1 micrograms/ml) comparable to those found in human serum after oral administration of amantadine revealed that rimantadine produced significantly longer protection than amantadine against virus-induced cytopathic effects. Correspondingly, rimantadine produced a comparable protective effect at four- to eight-fold-lower concentrations than amantadine. Both drugs produced increasing and similar effects at higher concentrations, which were comparable to those reported in nasal washings after aerosol administration of amantadine. At the concentrations tested, amantadine was nontoxic. However, at concentrations of 16 and 32 micrograms/ml, rimantadine was toxic to the ciliated epithelium after 10 to 21 days of continuous exposure. When the drugs were added 24 h or more after infection, protection against cytopathic effects decreased markedly. Both drugs moderately suppressed virus production at concentrations of 0.5 to 16 micrograms/ml. However, no dose response or difference between the drugs was observed. Because of comparable antiviral activity at lower concentrations and greater activity at similar concentrations, rimantadine may be more useful than amantadine for oral prophylaxis and therapy of influenza.